Measuring the Effectiveness of Blended Learning in the Post‑Pandemic Era: A Comparative Quantitative Analysis of Flipped Classroom and Hybrid Flexible (HyFlex) Models on Cognitive Achievement and Student Engagement in Indonesian Senior High Schools - Lindawati, Lindawati; Mendrofa, Netti Kariani; Wahdah; Ahmadin; A. Fitriani (PT Inovasi Pratama Internasional, 2026)
The COVID‑19 pandemic accelerated the adoption of blended learning across Indonesian senior high schools (SMA), but systematic evidence comparing different blended models remains limited. This quantitative study conducts a comparative secondary data analysis of flipped classroom–based blended learning and Hybrid Flexible (HyFlex) models with respect to cognitive achievement and student engagement at the upper‑secondary level. Drawing on a national meta‑analysis of blended learning in Indonesia (27 studies, 2016‑2020), quasi‑experimental studies of flipped classroom implementations in SMA, and international HyFlex evaluations, the study synthesizes standardized mean differences, mean score differences, and survey‑based engagement indicators. Blended learning overall demonstrates a large positive effect on Indonesian students’ learning outcomes, including at senior high school (SMD ≈ 1.00 vs conventional instruction). Within this, flipped classroom–based blended learning yields substantial gains in critical thinking and other higher‑order cognitive outcomes, although effects on writing performance depend strongly on students’ self‑regulation. HyFlex implementations at the tertiary level generally match face‑to‑face instruction in cognitive outcomes but produce mixed patterns in grade distributions and student satisfaction. The discussion interprets these findings for Indonesian SMA in the post‑pandemic context, arguing that flipped classroom designs have stronger empirical support than HyFlex for raising cognitive achievement and structured engagement under current infrastructural and policy conditions